2010
DOI: 10.1124/jpet.110.166884
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Acute Kidney Injury via A1Adenosine Receptor-Mediated Akt Activation Reduces Liver Injury after Liver Ischemia and Reperfusion in Mice

Abstract: Hepatic ischemia reperfusion (IR) injury causes acute kidney injury (AKI). However, the contribution of AKI to the pathogenesis of liver IR injury is unclear. Furthermore, controversy still exists regarding the role of A 1 adenosine receptors (A 1 ARs) in AKI. In this study, we determined whether exogenous and endogenous A 1 AR activation protects against AKI with subsequent liver protection after hepatic IR in mice. We found that after hepatic IR A 1 knockout (KO) mice and A 1 AR antagonisttreated A 1 wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…Accumulated evidence suggests that A1R play a role in the protection from I/R injury in several organs such as heart, brain, and lung [12][13][14][26][27][28][29][30][31][32][33][34][35][36][37] through mechanisms that remain to be defined. The present study suggests that A1R activation prevents I/R injury through the control of OXPHOS efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulated evidence suggests that A1R play a role in the protection from I/R injury in several organs such as heart, brain, and lung [12][13][14][26][27][28][29][30][31][32][33][34][35][36][37] through mechanisms that remain to be defined. The present study suggests that A1R activation prevents I/R injury through the control of OXPHOS efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of A1R has been shown to protect liver from I/R injury via pathways involving Akt [13]. Taking into account that activated Akt decreases GSK-3β activity, which is related with modulation of the MPT, we probed if the protective effect of preconditioning against hepatic I/R injury involves the activation of the Akt/GSK-3β signaling pathway to prevent mitochondria-mediated I/R injury.…”
Section: Phosphorylation Status Of Akt and Gsk-3βmentioning
confidence: 99%
See 2 more Smart Citations
“…This is likely mediated by transcription factor Sp1 and is a potential therapeutic target for the treatment of liver ischaemia [117]. This also has renal implications as well, as one study demonstrated that activation of renal A 1 receptors was protective for the liver as well as kidney after liver ischaemia reperfusion injury [198].…”
Section: Ischaemia and Vascular Injurymentioning
confidence: 99%